Poverty in Germany — Impact of Corona Pandemic Not Yet Assessable - Judith Niehues (Wirtschaftsdienst)
Abstract While the risk of poverty increased quite markedly around the turn of the millennium, a further but flatter increase can be subsequently observed. The development was also accompanied by a stronger increase in the at-risk-of-poverty threshold, particularly in the wake of the positive income trend in the years prior to the coronavirus pandemic. The extent to which the corona pandemic influenced poverty cannot yet be assessed, as the results published so far are not comparable with previous years due to a break in the available time series. However, first indications of simulation studies suggest that the relative risk of poverty and the distribution of disposable income may have changed only slightly.